The Star, 12 May 2010 (Star Publications, 2010)
Mexico's Carlos Slim beat Bill Gates and Warren Buffett for the top spot on Forbes magazine's annual list of billionaires, becoming the first person from outside the United States to lead the rangkings in 16 years.